Mister Exam
Lang:
EN
EN
ES
RU
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
Identical expressions
(two *log(three *x) - three)/x^ three = zero
(2 multiply by logarithm of (3 multiply by x) minus 3) divide by x cubed equally 0
(two multiply by logarithm of (three multiply by x) minus three) divide by x to the power of three equally zero
(2*log(3*x) - 3)/x3 = 0
2*log3*x - 3/x3 = 0
(2*log(3*x) - 3)/x³ = 0
(2*log(3*x) - 3)/x to the power of 3 = 0
(2log(3x) - 3)/x^3 = 0
(2log(3x) - 3)/x3 = 0
2log3x - 3/x3 = 0
2log3x - 3/x^3 = 0
(2*log(3*x) - 3) divide by x^3 = 0
Similar expressions
(2*log(3*x) + 3)/x^3 = 0
(2*log(3*x) - 3)/x^3 = 0 equation
+ equation
Solve the equation!
The unknown in the equation:
v
Numerical solution:
Do search numerical solution at [
,
]